Characterization of Cd1-xZnxSe thin films deposited at low temperature by chemical route - Hankare, P. P.; Chate, P. A.; Asabe, M. R.; Delekar, S. D.; Mulla, Imtiaz S.; Garadkar, K. M. (Journal of Materials Science-Materials in Electronics, 2006)
Optoelectronic technologically important pseudo-binary Cd1-xZnxSe thin films with a variable composition ( 0 < x < 1) has been developed by chemical bath deposition method. The objective to study growth kinetics, physical, microscopic, compositional, optical, electrical and structural changes. Cd1-xZnxSe have been deposited on non-conducting glass substrate in tartarate bath containing Cd+2 and Zn+2 ions with sodium selenosulphate with an aqueous alkaline medium at 278 K. The quality and the thickness of the films are depends upon deposition temperature, deposition time and pH, etc. X-ray diffraction (XRD), atomic absorption spectroscopy, optical absorption, scanning electron microscopy and thermoelectric technique characterized the films. The XRD study indicates the polycrystalline nature in single cubic phase over whole range of composition. Analysis of absorption spectra gave direct type band gap, the magnitude of which increases non-linearly as zinc content in the film is increased and dc electrical conductivity at room temperature was found to decreases from 10(-7) to 10(-8) (Omega cm)(-1). All the films show n-type conductivity. The promising features observed are the formation of continuous solid solutions in a single cubic phase.

Effect of annealing on properties of ZrSe2 thin films - Hankare, P. P.; Asabe, M. R.; Kokate, A. V.; Delekar, S. D.; Sathe, D. J.; Mulla, Imtiaz S.; Chougule, B. K. (Journal of Crystal Growth, 2006)
Thin films of ZrSe2 have been prepared on stainless steel and fluorine-doped tin oxide-coated glass substrates using electrodeposition technique at potentiostatic mode. Double-distilled water containing precursors Zr and Se with ethylene diamine tetra-acetic acid disodium salt as a complexing agent was used to obtain good quality deposits by controlling the rate of reaction. The preparative parameters such as concentration of bath, deposition time, bath temperature, pH of the bath and annealing temperature have been optimized using photoelectrochernical (PEC) technique. The films deposited at optimum preparative parameters are annealed at different temperatures. The film annealed at 200 degrees C shows more photosensitivity. The as-deposited and annealed films at 200 degrees C have been characterized by X-ray diffraction (XRD), energy dispersive analysis by X-ray (EDAX), optical absorption and scanning electron microscopy (SEM). The XRD analysis of the as-deposited and annealed films showed the presence of polycrystalline nature with hexagonal crystal structure. EDAX study reveals that deposited films are almost stoichiometric. Optical absorption study shows the presence of direct transition and band gap energies are found to be 1.5 and 1.38 eV, respectively, for the as-deposited and annealed films. SEM study revels that the grains are uniformly distributed over the surface of substrate for the as-deposited as well as annealed film, which indicates formation of good and compact type of crystal structure. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: band gap; EDAX; Electrodeposition; PEC; SEM; XRD; ZrSe2 thin films

Novel chemical synthetic route and characterization of zinc selenide thin films - Hankare, P. P.; Chate, P. A.; Delekar, S. D.; Asabe, M. R.; Mulla, Imtiaz S. (Journal of Physics and Chemistry of Solid, 2006)
Zinc selenide (ZnSe) thin film have been deposited using chemical bath method on non-conducting glass substrate in a tartarate bath containing zinc sulfate, ammonia, hydrazine hydrate, sodium selenosulfate in an aqueous alkaline medium at 333 K. The deposition parameter of the ZnSe thin film is interpreted in the present investigation. The films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), optical absorption, electrical measurements, atomic absorption spectroscopy (AAS). The ZnSe thin layers grown with polycrystalline zinc blende system along with some amorphous phase present in ZnSe film. The direct optical band gap `E-g' for the film was found to be 2.81 eV and electrical conductivity in the order of 10(-8)(Omega cm)(-1) with n-type conduction mechanism. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: chalcogenides; electronic materials

Photoelectrochemical properties of electrochemically deposited CdIn2S4 thin films - Kokate, A. V.; Asabe, M. R.; Delekar, S. D.; Gavali, L. V.; Mulla, Imtiaz S.; Hankare, P. P.; Chougule, B. K. (Journal of Physics and Chemistry of Solids, 2006)
Thin films of CdIn2S4 have been deposited on to stainless steel and fluorine-doped tin oxide (FTO)-coated glass substrates from aqueous acidic bath using an electrodeposition technique. Ethylene diamine tetra-acetic acid (EDTA) disodium salt is used as complexing agent to obtain good-quality deposits by controlling the rate of the reaction. The different preparative parameters like concentration of bath, deposition time, bath temperature, pH of the bath have been optimized by the photoelectrochemical (PEC) technique in order to get good-quality photosensitive material. Different techniques have been used to characterize CdIn2S4 thin films. Optical absorption shows the presence of direct transition with band gap energy 2.17 eV. The X-ray diffraction (XRD) analysis of the as-deposited and annealed films showed the presence of polycrystalline nature. Energy-dispersive analysis by X-ray (EDAX) study for the sample deposited at optimized preparative parameters shows that the In-to-Cd ratio is almost 2 and S-to-Cd ratio is almost 4. Scanning electron microscopy (SEM) for samples deposited at optimized preparative parameters reveals that spherical grains are uniformly distributed over the surface of the substrate indicates the well-defined growth of polycrystalline CdIn2S4 thin film. PEC characterization of the films is carried out by studying photoresponse, spectral response and photovoltaic output characteristics. The fill factor (ff) and power conversion efficiency (eta) of the cell are 69 and 2.94%, respectively. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Thin films; X-ray diffraction

Synthesis of cadmium selenide thin films at low-temperature by simple chemical route and their characterization - Hankare, P. P.; Delekar, S. D.; Asabe, M. R.; Chate, P. A.; Bhuse, V. M.; Khomane, A. S.; Garadkar, K. M.; Sarwade, B. D. (Journal of Physics and Chemistry of Solids, 2006)
Crystalline CdSe thin film has been deposited using appropriate precursor solution containing cadmium sulfate octahydrate, tartaric acid, potassium hydroxide, ammonia and sodium selenosulfate. The effect of parameters such as bath composition, deposition temperature, pH of the solution, speed of the rotation and the specificity of complexing agent on growth process is studied. The `as-deposited' CdSe thin film was found to be red in color, specularly reflective and well adherent to the glass substrate. The crystalline phase of the deposited sample was hexagonal wurtzite-type. The analysis of optical absorption data shows energy band gap energy (E-g) 2.01 eV. The morphological study and compositional analysis of film sample have been discussed. The electrical resistivity of CdSe thin film was found to the order of 10(6) Omega cm. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: XRD

Synthesis, characterization of chemically deposited indium selenide thin films at room temperature - Asabe, M. R.; Chate, P. A.; Delekar, S. D.; Garadkar, K. M.; Mulla, Imtiaz S.; Hankare, P. P. (Journal of Physics and Chemistry of Solids, 2008)
Polycrystalline In2Se3 semiconducting thin films were prepared by using relatively simple chemical bath deposition method at room temperature by the reaction between indium chloride, tartaric acid, hydrazine hydrate and sodium selenosulphate in an aqueous alkaline medium. Various preparative conditions of thin film deposition are outlined. The as grown films were found to be transparent, uniform, well adherent and red in color. The films were characterized using X-ray diffraction (XRD), scanning electron microscopy, atomic absorption spectroscopy and energy dispersive atomic X-ray diffraction (EDAX). The XRD analysis of the film showed the presence of polycrystalline nature with hexagonal crystal structure. SEM study revels that the grains are homogenous, without cracks or pinholes and well covers the glass substrate. The optical absorption and electrical conductivity was measured. The direct optical band gap value for the films was found to be of the order of 2.35eV at room temperature and have specific electrical conductivity of the order of 10(-2) (Omega cm)(-1) showing n-type conduction mechanism. The utility of the adapted technique is discussed from the view-point of applications considering the optoelectric and structural data. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Semiconductor

Photoelectrochemical applications of In2Se3 thin films by chemical deposition - Hankare, P. P.; Rathod, K. C.; Asabe, M. R.; Jadhav, A. V.; Helavi, V. B.; Chavan, Santosh S.; Garadkar, K. M.; Mulla, Imtiaz S. (Journal of Materials Science-Materials in Electronics, 2011)
Indium selenide films have been synthesized by chemical bath deposition method onto stainless steel plate. The configuration of fabricated cell is n-In2Se3| NaOH(1 M) + S(1 M) + Na2S(1 M) |C-(graphite). Characterization of the photoelectrochemical cell was carried out by studying X-ray diffraction, current-voltage and capacitance-voltage characteristics in the dark, barrier height measurements, power output, photoresponse and spectral response. The study shows that the In2Se3 thin films are n-type semiconductor. The junction ideality factor was found to be 3.24. The flat band potential and the barrier height were found to be 0.720 V and 0.196 eV, respectively. From the study of power output characteristics, open circuit voltage, short circuit current, fill factor and efficiency were found to be 310 mV, 20 mu A, 37.64 and 0.61%, respectively. Photoresponse studies show that the lighted ideality factor is 2.78. Maximum current was observed at 575 nm.